Comparison of Chinese and Danish Soil Legislation Based on Soil Heavy Metal Values in Contaminated Sites: A Case Study in Sichuan. Issue 3 (2nd April 2020) - Liu, Wei; Liu, Shuyuan; Li, Xujie; Wang, Yanni; Li, Yunzhen; Mou, Zishen
ABSTRACT: We conducted rapid detection and laboratory detection of eight heavy metals in soils at two contamination sites in Luxian County, Sichuan, China, and compared the values by the two different methods. Meanwhile, the laboratory detection results were compared with the regional background values and the standard values of China and Denmark. This study further discusses the laws and regulations, regulatory policies and technical guiding principles of China and Denmark. The rapid detection method is convenient and inexpensive, but results in an over-estimation of pollution. Being commonly used in soil pollution characterization in Denmark, the rapid detection method can serve as a supplementary tool for a quick screening of pollutants prior to laboratory analysis for characterizing soil contamination. While Denmark has already established comprehensive laws and technical guidelines, China is in the process of improving legislation and establishing detailed guidelines. The legal system, research, exploration, and experience of soil pollution prevention and control in Denmark can provide a meaningful reference for the decision-making management and legal system construction of soil pollution prevention and control in China.